2022
DOI: 10.35940/ijmh.h1460.048822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Career Counselling on Employee Performance in Murang’a Water and Sanitation Company Limited

Abstract: Career counseling is a career development initiative in which career education is provided to workers by career counselors to help them appreciate their motivations, explain their objectives, commit to action, navigate career transitions, and learn how they can contribute to the organization's overall effectiveness. The fundamental aims of counseling are to foster behavioral improvement, support decision-making, facilitate the capacity of clients, develop coping skills and improve relationships. Employee perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The career development of the employees within the organization enhances their employee retention levels and motivation aspects. The role of the employee career development in enhancing their motivation and retention levels have been noted by (Kathukya & Machogu, 2021), (Kathukya et al, 2022) and (Joshi et al, 2021) have linked the employee career development to the Employee attitude survey in our organization always focuses on the work climate aspects to a large extent (M = 3.5371, SD = 1.08148). The work climate aspects ensures that the employees are comfortable in their work thus leading to improvement in employee job satisfaction.…”
Section: Descriptive Statisticsmentioning
confidence: 91%
“…The career development of the employees within the organization enhances their employee retention levels and motivation aspects. The role of the employee career development in enhancing their motivation and retention levels have been noted by (Kathukya & Machogu, 2021), (Kathukya et al, 2022) and (Joshi et al, 2021) have linked the employee career development to the Employee attitude survey in our organization always focuses on the work climate aspects to a large extent (M = 3.5371, SD = 1.08148). The work climate aspects ensures that the employees are comfortable in their work thus leading to improvement in employee job satisfaction.…”
Section: Descriptive Statisticsmentioning
confidence: 91%
“…Therefore, the financial and non-financial objectives serve as the foundation for the personal reward. Ngatia (2017) applied this theory in the course of analyzing the effects of non-monetary rewards on service provision, and they found that it was significant. Mutie, Muturi, and Njeru (2019), who made use of equity theory when analyzing financial rewards, conducted a similar study in Kenya.…”
Section: Theoretical Literature Reviewmentioning
confidence: 99%
“…After analyzing the effects of demographic variables and perceived organizational career management, Kathukya and Machogu (2021) found that career flexibility performed a distinct role in predicting pay. These connections were mediated by professional satisfaction.…”
Section: Career Management On Employee Performancementioning
confidence: 99%